Modelling in relation to cation ordering - Dove, M; Bosenick, A; Myers, E; Warren, M; Redfern, S (Gordon and Breach Science Publ Inc, 2000)
We review the methodology of using computer models to obtain quantitative information about cation ordering. Empirical interactomic potentials or ab initio electronic structure calculations are used to generate the energies for many configurations containing disordered arrangements of cations, and the parameters in model Hamiltonians can be determined from these energies. Monte Carlo simulations are then used to generate ensemble averages as functions of temperature or chemical composition. Analysis of the Monte Carlo ensembles directly yields the temperature dependence of long-range and short-range order, and thermodynamic quantities such as energy and heat capacity. Use of thermodynamic integration allows for the calculation of entropy and free energy. The methods are illustrated by examples showing long-range order/disorder phase transitions (feldspars), short-range order in solid solutions (pyrope-grossular), and non-convergent ordering (magnesium aluminate spinel); where comparisons with experimental data are possible, the model calculations are seen to give results that are reasonably accurate. The example in which ab initio electronic structure calculations are used show that it is now possible to extract accurate thermodynamic data for ordering processes using models that require no prior experimental data.